2019
DOI: 10.1007/s13398-019-00738-w
|View full text |Cite
|
Sign up to set email alerts
|

Mean ergodic composition operators on generalized Fock spaces

Abstract: Every bounded composition operator C ψ dened by an analytic symbol ψ on the complex plane when acting on generalized Fock spaces F p ϕ , 1 ≤ p ≤ ∞, is power bounded. Mean ergodic and uniformly mean ergodic composition operators on the spaces are characterized. The set of periodic points of these operators is also determined. Theorem 1.1. (Theorem 2.1 of [18], Theorem 2.1 of [19]) Let 1 ≤ p ≤ ∞ and ψ be a nonconstant analytic map on the complex plane C. Then the operator C ψ : F p ϕ → F p ϕ is 1 *Corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The monographs [14,28] provides basic information on ergodic theory. Inspired by all these works, the authors and J. Bonet in [26] studied the mean ergodicity of composition operators acting on generalized Fock spaces, and concluded that all bounded composition operators on Fock spaces F p are power bounded whenever 1 ≤ p ≤ ∞. In this section, we show that this conclusion is no longer true in general for the weighted composition operators W (u,ψ) .…”
Section: Power Bounded W (Uψ)mentioning
confidence: 72%
See 1 more Smart Citation
“…The monographs [14,28] provides basic information on ergodic theory. Inspired by all these works, the authors and J. Bonet in [26] studied the mean ergodicity of composition operators acting on generalized Fock spaces, and concluded that all bounded composition operators on Fock spaces F p are power bounded whenever 1 ≤ p ≤ ∞. In this section, we show that this conclusion is no longer true in general for the weighted composition operators W (u,ψ) .…”
Section: Power Bounded W (Uψ)mentioning
confidence: 72%
“…(ii) Let 1 ≤ p ≤ ∞,and ψ(z) = az with |a| = 1. If both u(0) and a are roots of unity, then W (u,ψ) is uniformly mean ergodic on F p .By a result in[26], the composition operator C ψ is not uniformly mean ergodic on F ∞ whenever |a| = 1. Now the weight function u makes it possible to enrich uniformity by taking the value |u(0)| smaller.Proof.…”
mentioning
confidence: 99%
“…The monographs [14,28] provide basic information on ergodic theory. Inspired by all these works, the authors and J. Bonet [26] studied the mean ergodicity of composition operators acting on generalized Fock spaces and concluded that all bounded composition operators on Fock spaces F p are power bounded whenever 1 ≤ p ≤ ∞. In this section, we show that this conclusion is no longer true in general for the weighted composition operators W (u,ψ) .…”
Section: Introductionmentioning
confidence: 77%
“…For further information related to the theory of Fock spaces we refer to mentioned monograph [14]. See also the recent works [8,10] on composition operators on the Fock space.…”
Section: Fock Spaces and Gaussian Integral Meansmentioning
confidence: 99%